Evaluation of the impact of immunization policies, including the addition of pharmacists as immunizers, on influenza vaccination coverage in Nova Scotia, Canada: 2006 to 2016 - Jennifer E. Isenor; Beth A. O'Reilly; Susan K. Bowles (BMC, 2018)
Abstract Background Influenza is a serious public health concern, resulting in morbidity, mortality and significant expense to healthcare systems worldwide. Annual vaccination is the most effective way to prevent influenza. The National Advisory Committee on Immunization in Canada recommends that everyone six months of age and older without contraindications should be vaccinated. The Canadian province of Nova Scotia implemented a publicly-funded universal influenza vaccination program in the 2010-2011 influenza season. In 2013, pharmacists in Nova Scotia gained the authority to provide a variety of vaccinations, including the publicly-funded influenza vaccine. This study aimed to investigate any changes in influenza vaccine coverage following the implementation of each policy change: 1) universal publicly-funded program and 2) universal publicly-funded program with the addition of pharmacists. Methods Influenza seasons evaluated were from 2006-2007 to 2015-2016. Coverage was estimated by examining Nova Scotia census data with aggregate immunization administration data, including the total number of vaccinations administered according to vaccine provider (physician, public health or pharmacist), geographic region, vaccine recipient age and year. Results The analysis showed an increase in influenza vaccine coverage immediately following the implementation of the two studied policy changes. Vaccine coverage increased from 36.4 to 38% following the implementation of the universally funded vaccine policy. Following the implementation of pharmacists as immunizers, coverage increased from 35.7 to 41.7%. Vaccine coverage was highest in those 65 years of age and older during all years evaluated. Physicians provided the highest proportion of vaccines during all study periods, however a decreasing trend through all periods was observed. Physicians proportionately provided more vaccines in urban areas; whereas pharmacist and public health immunization providers in rural areas provided proportionately more vaccinations than their urban counterparts. Conclusions The addition of a universally funded vaccination policy and the addition of pharmacists as providers of the influenza vaccine resulted in increases in vaccine coverage initially. Additional research is needed to determine the long-term impacts of the policy changes on vaccination coverage and to identify other important factors affecting vaccine uptake.